The systemic lupus erythematosus–associated single nucleotide polymorphism rs1143678 in integrin αM cytoplasmic tail generates a 14-3-3ζ binding site that is proinflammatory - Ong, Li-Teng (2019)
The leukocyte integrin αMβ2 (CR3 or Mac-1) has both proinflammatory and immune regulatory functions. Genome-wide association studies have identified several ITGAM (αM subunit) single nucleotide polymorphisms that are associated with systemic lupus erythematosus. The single nucleotide polymorphism rs1143678 substitutes Pro1146 for Ser in the integrin αM cytoplasmic tail. A detailed functional characterization of this substitution is lacking. Using transfected human cell lines, reconstituted mouse bone marrow neutrophils, and bone marrow–derived macrophages (BMDMs), we showed that P1146S (PS) substitution promoted integrin αMβ2–mediated adhesion, spreading, and migration of cells on iC3b and fibrinogen. In the presence of LPS together with iC3b or fibrinogen, the expression levels of IL-6 and TNF-α in integrin αM(PS)β2 BMDMs were significantly higher than those of integrin αM(wild-type)β2 BMDMs, and they showed faster kinetics of Erk1/2 activation through the src family kinase(s)–Syk signaling pathway. Integrin αM(PS)β2 BMDMs also exhibited higher levels of active RhoA and phagocytic activity. Mechanistically, P1146S substitution in the αM cytoplasmic tail generates a noncanonical 14-3-3ζ binding site that modulates integrin αM(PS)β2 outside-in signaling.